Effect of Nutrient Management on Growth, Yield and Nutrient Uptake in Sorghum (Bangladesh Agronomy Journal, 2025)
A two-year field study was conducted at Agronomy Research Field, BARI, Gazipur, during rabi season of 2023-2024 and 2024-2025 to evaluate the effect of nutrient management on the  growth,  yield  and  nutrient  uptake  of  sorghum.  The  experiment  was  conducted  in Randomized Complete Block Design (RCBD) with 3 replications consisting five treatments 12viz., T: 150-75-62.5-33.75-2.8-1.4 kg haof N-P-K-S-Zn-B; T: 120-60-50-27-2.8-1.4 -1 34kg haof N-P-K-S-Zn-B; T: 90-45-37.5-20.25-2.8-1.4 kg haof N-P-K-S-Zn-B; T: 60- -1 -1 530-25-13.5-2.8-1.4 kg haof N-P-K-S-Zn-B; T: Control (Native fertility).The unit plot size -1 was 3.6m × 3.6m. BARI Sorghum-1 seeds were sown on 29 November 2023 and  1 December 2024, respectively. Plant spacing was maintained at 60 cm × 10 cm. One third of N and other fertilizer were applied as basal at final land preparation. The rest N was applied at 25 and 50 DAS in equal splits. Data for growth analysis were taken at 35 days after sowing (DAS), 55 DAS, 75 DAS, 95 DAS and 115 DAS in the year of 2023-2024. Chlorophyll content was measured using a SPAD meter (Model SPAD-502, Minolta crop, Ramsey, NJ). The yield component data was taken from randomly selected 10 plants prior to harvest from each plot. At harvest, the yield data was recorded plot wise. The collected data were analyzed statistically and means were adjudged by LSD test at 5% level of significance using Statistics 10. The highest SPAD value was observed at 60 DAS which declined gradually reaching the lowest at 90 DAS in all treatments. The highest SPAD values were 1 observed in Ttreatment (28.1 at 35 DAS to 45.8 at 115 DAS) in the growing season. The results indicated that higher nutrient level showed higher SPAD values. The total dry matter (TDM) accumulation was slower up to 55 DAS then increased rapidly up to 95 DAS and afterwards increased slowly up to harvest. TDM accumulation was higher (1316 g m ) at-2 11 harvest in higher dose of fertilizer (T) applied. Ttreatment (150-75-62.5-33.75-2.8-1.4 kg  haof N-P-K-S-Zn-B) produced the highest yield (4.5 t hain 2023–2024 and 3.9 t hain -1 -1 -1  1 2024–2025). The 1000-grain weight was also found higher in T(39.5 g in 2023–2024). Nutrient uptake (N-P-K-S-Zn-B) showed a positive correlation with sorghum grain yield.  Nutrient concentrations and uptake were influenced by Nutrient levels.Bangladesh Agron. J. 2025, 28(1): 89-94